The Effect of Using Take and Give Models With Contextual Approaches On Mathematics Learning Outcomes - Yuliana Setiawati; Tri Novita Irawati (Universitas Islam Jember, 2019)
Learning model greatly influences student learning outcomeson certain subjects. While learning outcomes are a goal of learning activities throught conscious effort carried out systematically. The researcher took studedent class VII SMP Islam Bustanul Arifin. This study aims to determine the effect of the use of take and give models with contextual approaches to learning outcomes in set material. This type is experimental research and quantitative approaches. Based on the results of thr research that was carried out to produce dan . By comparing the values obtained that . This means that the alternative hypothesis is accepted, so there is an influences from the use of take and give models with contextual approaches to student learning outcomes. Keywords: take and give, learning outcomes